Antonio García-Fresca Tolosana: a councilman “trom Pamplona” in the Institutes of Pamplona and Tudela - Martínez Lacabe, Eduardo (Huarte de San Juan. Geografía e Historia, 2011)
Antonio García-Fresca (1899-1965), received his bachelor’s degree in Natural Sciences and obtained a PhD in Entomology. He devoted part of his life to research and education, and was awarded a scholarship by the British Museum of Natural History. During his years in education, he was the chair of the science departments at the Institute of Pamplona, Santander and at the Instituto Obrero Blasco Ibanez in Valencia. He belonged to a Basque family of long liberal tradition, and his republican militancy led him to appear as a candidate for the Republican Party in the municipal elections; He obtained the Councilman’s Record of Pamplona in 1931. He was in Madrid at the beginning of the Civil War, which saved him from a certain death, and was disqualified by the Pro-Franco authorities to exercise as a Professor. He passed away in Tenerife (1965) shortly after being restored to his position.